2020
DOI: 10.3390/su12176941
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change—Challenges and Response Options for the Port Sector

Abstract: Climate change is an established and growing priority environmental issue. This paper investigates the importance of climate change in ports through a research-based survey on data collected from participants at the Greenport Congress in Valencia in 2018. The data for this paper were obtained from the responses of 55 port professionals and environmental specialists that replied to a questionnaire survey during the Congress. Questionnaires were analyzed to identify the opinions and experience of delegates. A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Also, they provided valuable insights into the importance of energy efficiency, demand response management, and sustainable port operations in saving energy costs [35]. A questionnaire survey among port professionals and environmental specialists in Valencia showed that among the top 10 environmental priorities for ports, Climate Change comes in at 6th, while Carbon Footprint sits at 8th [27]. A survey of 70 maritime sector leaders in Ireland refers to a significant lack of understanding of climate change [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, they provided valuable insights into the importance of energy efficiency, demand response management, and sustainable port operations in saving energy costs [35]. A questionnaire survey among port professionals and environmental specialists in Valencia showed that among the top 10 environmental priorities for ports, Climate Change comes in at 6th, while Carbon Footprint sits at 8th [27]. A survey of 70 maritime sector leaders in Ireland refers to a significant lack of understanding of climate change [7].…”
Section: Discussionmentioning
confidence: 99%
“…Also, given the limited knowledge of port attitudes toward climate action, 18 Chinese organizations were investigated [26]. In addition, a questionnaire survey among port professionals and environmental specialists in Valencia shed light on the crucial role of climate change in port operations [27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil quality and terrestrial habitats are the issues with the lowest percentage of ports monitoring them. Concerning Carbon Footprint, although there has been an increase of interest related to Climate Change issues (as presented in Table 16), monitoring this issue is rather complicated due to the amount of data necessary to gather, the personnel involved and the resources needed (Azarkamand et al, 2020). This could explain the steady trend of this environmental monitoring indicator.…”
Section: Environmental Monitoringmentioning
confidence: 99%
“…The production and operation activities of ports consume large amounts of energy, which results in serious carbon dioxide emission problems [1]. With the increasingly serious problem of climate change, ports have put forward higher requirements for their emission reduction performance [2,3]. Port equipment emissions are the main source of carbon dioxide emissions in port areas.…”
Section: Introductionmentioning
confidence: 99%